HUBUNGAN KETERLIBATAN ORGANISASI MAHASISWA DAN KEMAMPUAN SOFT SKILLS DALAM MENUNJANG KARIR (STUDI KASUS FEB UNIVERSITAS MUHAMMADIYAH MAKASSAR) - H, Aswinda; Aisyah, Siti; Nasrullah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effects of student organizational involvement and soft skills on career support among students of the Faculty of Economics and Business, Muhammadiyah University of Makassar. The research employed a quantitative approach with a sample of 96 respondents. The data were analyzed using multiple linear regression with the assistance of SPSS, supported by validity, reliability, and classical assumption tests. The results show that partially, student organizational involvement has a positive and significant effect on career support (t = 1.983; sig. = 0.050 ≤ 0.05). Soft skills also have a positive and significant effect on career support (t = 4.114; sig. = 0.000 ≤ 0.05). The coefficient of determination (R²) is 0.756, indicating that 75.6% of the variation in career support is explained by the independent variables, while the remaining 24.4% is explained by other variables outside this study. Soft skills are the most dominant variable in supporting students’ career development.